Multi-epitope chimeric vaccine design against emerging Monkeypox virus via reverse vaccinology techniques- a bioinformatics and immunoinformatics approach - Aiman, Sara; Alhamhoom, Yahya; Ali, Fawad; Rahman, Noor; Rastrelli, Luca; Khan, Asifullah; Farooq, Qurat ul Ain; Ahmed, Abbas; Khan, Asif; Li, Chunhua (Frontiers in Immunology, 2022)
The emerging monkeypox is a zoonotic orthopoxvirus that causes infections in humans similar to smallpox. Since May 2022, cases of monkeypox have been increasingly reported to the World Health Organization (WHO) worldwide. There are no clinically validated treatments for monkeypox infection. In this study, an Immunoinformatics approach was used to identify potential vaccine targets against monkeypox. A total of 190 MPXV-2022 proteins were retrieved from the ViPR database and subjected to various analyses including antigenicity, allergenicity, toxicity, solubility, IFN-γ, and virulence. Three outer-membrane and extracellular proteins were selected based on the respective parameters to predict B-cell and T-cell epitopes. Nine overlapping MHC-I, MHC-II, and B-cell epitopes were selected to design multi-epitope vaccine constructs linked with suitable linkers in combination with different adjuvants to enhance the immune responses of the vaccine constructs. Molecular modeling and structural validation ensured high-quality 3D structures of vaccine constructs. Based on various immunological and physiochemical properties and docking scores, MPXV-V2 was selected for further investigation. In silico cloning revealed a high level of gene expression of the MPXV-V2 vaccine within the bacterial expression system. Immune and MD simulations confirmed the molecular stability of the MPXV-V2 construct with high immune responses within the host cell. These results may help in experimental vaccine development against monkeypox with increased potency and improved safety.